2012
DOI: 10.1007/s00540-012-1486-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurolytic celiac plexus block reduces occurrence and duration of terminal delirium in patients with pancreatic cancer

Abstract: The duration and occurrence of TD and the pain severity were significantly less in pancreatic cancer patients who underwent neurolytic CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…(). The CAM, DOS and MMSE were used in other studies (Arai et al., ; Gagnon et al., ; Tatematsu et al., ). The use of different tools means identification of delirium varied between the studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(). The CAM, DOS and MMSE were used in other studies (Arai et al., ; Gagnon et al., ; Tatematsu et al., ). The use of different tools means identification of delirium varied between the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the research demonstrate that although there has been some investigation of the treatment of delirium in patients with advanced cancer, relatively few rigorous studies have been conducted. In terms of pharmacological interventions, the use of atypical antipsychotics reduced mean MDAS scores (Boettger & Breitbart, ; Breitbart et al., ), as did opioid rotation (Morita et al., and Moryl et al., ), a coeliac plexus block reduced the duration of terminal delirium (Arai et al., ), and methylphenidate was found to be effective in patients with hypoactive delirium (Gagnon et al., ). The one report of a nonpharmacological intervention found that the dose of antipsychotics could be reduced for patients participating in exercise therapy (Tatematsu et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations